MELESTARIKAN TRADISI: KEUNIKAN DAN KEINDAHAN AYUN LUCI DARI KERINCI - Jannah, Hidayatul; Nabila NA, Nazhira YA, Sindy LP, Thoyyibatu D, Kesintia DT, Helena, Nanda L, Jihan FM, Wiya AA, Anni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Ayun Luci is a traditional ceremony from the Kerinci community in Jambi Province, Indonesia, which holds deep spiritual and cultural values. This tradition is performed as an expression of gratitude and a prayer to God, seeking protection for rice crops during the grain-filling phase from pests and hoping for an abundant harvest. The ritual involves various cultural elements such as traditional chants (mantras), local culinary offerings, sacred symbols, and the performance of Asyeik dance accompanied by traditional music. However, in the face of modernization and globalization, the existence of this tradition is increasingly marginalized and at risk of extinction. The younger generation, as cultural successors, tend to be unfamiliar with the values and meanings embedded in such local wisdom. This study aims to explore strategies for preserving the Ayun Luci tradition through educational approaches, particularly by integrating traditional dance and music elements into learning activities at the elementary school level. Using a qualitative descriptive method through literature study, the research examines relevant sources related to culture-based education and traditional arts preservation. The findings reveal that developing Ayun Luci into a contextual performing art and incorporating it into local culture-based thematic learning can enhance students’ awareness and appreciation of cultural heritage. Furthermore, such integration promotes students’ artistic appreciation, strengthens cultural identity, and fosters a sense of pride in ancestral traditions. In conclusion, the preservation of Ayun Luci should not rely solely on customary communities but must also be supported by educational institutions. Through culturally responsive curriculum development, this tradition can be continually introduced, studied, and passed on to future generations in a sustainable manner.